Softening of the flux line lattice in Ge/Pb multilayers - Neerinck, D.; Temst, K.; Baert, M.; Osquiguil, E.; Van Haesendonck, C.; Bruynseraede, Y.; Gilabert, A.; Schuller, I.K. (IOP Publishing, 1992)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Katholieke Universiteit Leuven; Bélgica